PENGARUH UTANG LUAR NEGERI DAN EKSPOR NON MIGAS TERHADAP PRODUK DOMESTIK BRUTO INDONESIA - Ariza, Anggatia; Peronika, Reza (Jurnal Keuangan dan Perbankan Syariah, 2020)
The purpose of this study is to determine simultaneously and partially significant effect between external debt in the economic sector and non-oil and gas exports on gross domestic product in Indonesia. The method used in this study is an associative method with a quantitative approach, the data analysis used is multiple linear regression analysis with Eviews 10 application. The data used in this study is secondary data which includes foreign debt in the economic sector, non-oil and gas exports and gross domestic product in Indonesia in 2009-2018.The results of this study indicate: 1) The foreign debt variable in the economic sector has a significant effect on gross domestic product in Indonesia in 2009-2018, with a probability value of 0.0090 <0.05 and a positive value of 0.055817, which means that every time there is an increase in foreign debt in the economic sector, then Indonesia's gross domestic product will also increase. 2) The non-oil and gas export variable has no significant effect on gross domestic product in Indonesia in 2009-2018, with a probability value of 0.3622> 0.05 and a positive value of 5.464491, which means that every time there is an increase in non-oil and gas exports, then Indonesia's gross domestic product will also increase. 3) Simultaneously (jointly) foreign debt in the economic sector and non-oil and gas exports have a significant effect on gross domestic product in Indonesia with a probability value of 0.004397 <0.05.